IMPLEMENTASI PERANGKAT DIGITAL SIGNAL PROCESSING UNTUK SISTEM VISIBLE LIGHT COMMUNICATION - Syifaul Fuada; Angga Pratama Putra; Yulian Aska; Angga Pradana; Erwin Setiawan; Trio Adiono (Website, 2018)
In order to realize a high-speed visible light communication (VLC) system, digital signal processing (DSP) device is required, including the main processing unit, DAC, and ADC. This paper discusses the interface design of the DSP processing unit to 10-bit DAC and 12-bit ADC for VLC applications. The systems in DAC and ADC modules have been designed with a SoC- based approach by using processing unit based on FPGA Xilinx Zynq xc7z010-1CLG400C on the Avnet MicroZed board. The design of hardware-level-design (H/W SoC) is done by utilizing IP blocks from Xilinx using Vivado 2014.2. While the hardware-level-design (S/W SoC) is designed using Xilinx SDK 2014.2. The DSP receiver has been tested in several scenarios, the DAC module is able to convert 10-bit digital signals into analog signals in sinusoidal form and can adjust its output frequencies, while the ADC module is capable of processing the analog signals into 12-bit digital signals with two's complement format. Keywords: ADC, DAC, DSP, system on-chip, visible light communications Untuk mewujudkan sistem visible light communication dengan kecepatan tinggi, diperlukan perangkat DSP yang memadai, mencakup unit pemroses utama, DAC, dan ADC. Pada makalah ini dirancang interface dari pemroses utama terhadap DAC 10-bit dan ADC 12-bit untuk aplikasi sistem VLC. Sistem pada modul DAC dan ADC, dirancang dengan pendekatan system-on-chip (SoC) dengan menggunakan unit pemroses berbasis FPGA Xilinx Zynq xc7z010-1CLG400C pada board Avnet MicroZed. Perancangan H/W SoC dilakukan dengan memanfaatkan blok-blok IP dari Xilinx menggunakan Vivado 2014.2. Sementara pada S/W SoC dirancang dengan menggunakan Xilinx SDK 2014.2. Penerima DSP telah diuji dengan beberapa skenario, modul DAC mampu mengkonversi sinyal digital 10-bit menjadi analog dalam bentuk sinusiodal dan dapat diatur frekuensi outputnya, sedangkan modul ADC mampu mengolah sinyal analog menjadi sinyal digital 12-bit dengan format bilangan two’s complement. Kata kunci: ADC, DAC, DSP, Sistem on-Chip,visible light communication